Anti-neuroinflammatory 3-hydroxycoumaronochromones and isoflavanones enantiomers from the fruits of Ficus altissima Blume. (October 2022) - Yao, Jiaming; Qin, Qiuyi; Wang, Yihai; Zeng, Jia; Xu, Jingwen; He, Xiangjiu
Abstract: A phytochemical study on the fruits of Ficus altissima Blume (lofty fig) led to the isolation and structural elucidation of three pairs of enantiomeric 3-hydroxycoumaronochromones and two pairs of enantiomeric isoflavanones, including eight undescribed compounds. Their structures were determined based on a comprehensive analysis of NMR and HR-ESI-MS spectroscopic data, calculated 13 C NMR-DP4 plus analysis and the comparisons of experimental measurements of ECD with calculated ECD spectra by TDDFT or ECD plots in reported protocols. The inhibitory effects of the isolated enantiomers on NO production stimulated by LPS in microglial BV-2 cells were evaluated. Among them, ficusaltin D exhibited the most potent anti-neuroinflammatory activity, which inhibited the production of NO and the expression of iNOS, IL-6 and IL-1β and suppressed the NF-κB nuclear translocation in LPS-induced BV-2 cells, while its enantiomer displayed cytotoxicity. Graphical abstract: Eight undescribed enantiomers including 3-hydroxycoumaronochromones and 3-hydroxyisoflavanones were isolated from the fruits of Ficus altissima Blume. Their anti-neuroinflammatory activities were evaluated. Image 1 Highlights: Six undescribed enantiomeric coumaronochromones were obtained from Ficus altissima. DP4 plus analysis and TDDFT-ECD calculation were used to confirm the configuration. Ficusaltin D exhibited potent inhibitory effect on NO production in BV-2 cells.